5-HT3 receptor within the amygdaloid complex modulates pain hypersensitivity induced by empathy model of cohabitation with a partner in chronic pain condition in mice - Rodrigues Tavares, Lígia Renata [UNESP]; Pelarin, Vinícius [UNESP]; Baptista-de-Souza, Daniela [UNESP]; Pereira Ferrari, Daniele; Nunes-de-Souza, Ricardo Luiz [UNESP]; Canto-de-Souza, Azair [UNESP] (Taylor & Francis, 2021)
Cohabitation with a partner undergoing chronic pain induces pain hypersensitivity. Among a lot of other neurochemical pathways, the serotonin (5-HT) role, specifically the 5-HT3 receptor (5-HT3R), in the amygdala has never been evaluated in this model. Here we studied the effects of the amygdala’s chemical inhibition, its neuronal activation pattern, and 5-HT, 5-HIAA, and 5-HT turnover within the amygdala. Furthermore, the systemic and intra-amygdala 5-HT3R activation and blockade in mice that cohabited with a conspecific subjected to chronic constriction injury were investigated. Male Swiss mice were housed in partners for 28 days. The dyads were divided into two groups on the 14th day: cagemate nerve constriction (CNC) and cagemate sham (CS). On the 24th day, cagemates underwent a stereotaxic surgery (when necessary) and, on the 28th day, they were evaluated on the writhing test. The amygdala inactivation promotes pain-hypersensitivity behaviors in groups and dyads; cohabitation with a partner with chronic pain did not change FosB-labeled cells in the amygdala’s nucleus and increases 5-HT turnover in cagemates. Systemic and intra-amygdala 5-HT3R activation attenuated and enhanced the number of writhes, respectively. In contrast, 5-HT3R blockade reduced hypersensitivity pain response. Results suggest the involvement of amygdala serotonergic signaling via 5-HT3R in empathy-like behavior.
Keywords: 5-HT3 receptors; amygdala; Empathy; pain hypersensitivity 22 July 2021; serotonin